A Facile Approach for the Synthesis of Novel 1, 2, 4‐Triazolo[4, 3‐a]Pyridine Derivatives in Single Step. (5th May 2014) - Santhosh Kumar, G.; Kurumurthy, C.; Sambasiva Rao, P.; Veeraswamy, B.; Shanthan Rao, P.; Narsaiah, B.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>